2018
DOI: 10.7554/elife.33123
|View full text |Cite
|
Sign up to set email alerts
|

Prediction error and repetition suppression have distinct effects on neural representations of visual information

Abstract: Predictive coding theories argue that recent experience establishes expectations in the brain that generate prediction errors when violated. Prediction errors provide a possible explanation for repetition suppression, where evoked neural activity is attenuated across repeated presentations of the same stimulus. The predictive coding account argues repetition suppression arises because repeated stimuli are expected, whereas non-repeated stimuli are unexpected and thus elicit larger neural responses. Here, we em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
89
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(110 citation statements)
references
References 87 publications
(148 reference statements)
18
89
3
Order By: Relevance
“…Numerous subsequent functional magnetic resonance imaging (fMRI), magnetoencephalography (MEG), and electroencephalography (EEG) studies have reported modulations of RS by the probability of a repetition 45,46,58–67 (i.e., expectation) (but see Refs. 68–70). Also consistent with PP, and seemingly at odds with neural adaptation accounts, is evidence that unexpected repetitions evoke greater neural responses than frequent alternations 37 .…”
Section: Hypothesis 1: Error‐signaling Neural Responses To Sensory Stmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous subsequent functional magnetic resonance imaging (fMRI), magnetoencephalography (MEG), and electroencephalography (EEG) studies have reported modulations of RS by the probability of a repetition 45,46,58–67 (i.e., expectation) (but see Refs. 68–70). Also consistent with PP, and seemingly at odds with neural adaptation accounts, is evidence that unexpected repetitions evoke greater neural responses than frequent alternations 37 .…”
Section: Hypothesis 1: Error‐signaling Neural Responses To Sensory Stmentioning
confidence: 99%
“…4 for a recent review). Although some studies have reported that expected stimulus representations are dampened, 69,79,90,92,105,[109][110][111] others have found that this global suppression is attributable to the suppression of neurons tuned away from the expected stimulus feature, while the representation of the expected stimulus is actually sharpened c . 78,88,112 Interestingly, Marques et al 113 recently found that while backward inputs from rodent lateromedial visual area (LM) to V1 c When interpreting these results, it should be noted that these decoding analyses of global BOLD activity or singleunit responses did not segregate activity from the proposed error unit and expectation unit populations.…”
Section: Hypothesis 1: Summary and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, subjects participated in an orthogonal fixation task, which did not require top-down attention on the face images. Third, reported effects of stimulus predictability on the magnitude of RS are inconsistent across studies, stimuli, and measurements (Kaliukhovich DA and R Vogels 2011;Kovacs G et al 2013;Tang MF et al 2018;Vinken K et al 2018). Thus, while the prediction error account for RS is an appealing hypothesis, it does explain the presence of RS during our long-lagged paradigm.…”
Section: Theoretical Implicationsmentioning
confidence: 80%
“…To characterise the neural correlates of decision-making, we recorded brain activity using electroencephalography (EEG). We were primarily interested in measuring feature-specific brain responses to presented motion signals using population-tuning modelling of brain activity (31)(32)(33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%